A design approach for controlled blade-off in overspeeding turbines. (August 2022) - Eryilmaz, Ibrahim; Pachidis, Vassilios
Graphical abstract: Highlights: An overspeeding turbine disk is subjected to excessive centrifugal loading and may burst upon exceeding a certain limit. One method is to prevent a disk burst is blade shedding which is controlled blade off at a predetermined rotational speed. To control the progression of an overspeed event, a firtree based design approach was investigated. A parametric design space exploration has been carried out based on explicit finite element simulations using LS-DYNA software. Firtree contact angle is the key parameter to release the blades at speeds lower than the disk burst speed. Blade firtree and disk post contact friction coefficient parameter is a limiting parameter for the blade shedding. Abstract: Following a shaft failure or loss of load in a gas turbine engine, the turbine overspeeds due to the continuing expansion through the stage(s). The overspeed may result in hazardous conditions which have to be prevented. Several mitigation methods include the control system's response by shutting the fuel flow, mechanical friction to reduce turbine acceleration, and blade release at a predetermined rotational speed. The release of the blades not only terminates the gas torque which accelerates the disk, but also increases the disk burst speed at reduced centrifugal load. In this manuscript, a design space exploration is presented to avoid disk burst by blade-off in a civil large turbofan engine through a parametric design of blade firtree and disk post system. The firtree design parameters used in the study are the contact angle between the blade firtree and the disk post, firtree bottom flank angle, firtree flank length and firtree thickness with respect to the disk post. The LS-DYNA finite element software was used in the simulations to generate possible failure scenarios. These were 'disk burst' and 'blade-off'. Blade-off conditions manifested in two ways as a function of design parameters. The first type was blade release from serrations without disk post failure, and the second type was blade escape with disk post failure. Following the design space exploration, the effect of several design and material parameters on the design space was investigated. These parameters are; the contact friction coefficient between the blade firtree and disk post, firtree serration number, and the strain hardening behavior of the material.